Influence of intellectual capital creative economy and marketing mix of community enterprise success after COVID-19 crisis of Thailand - Petcharaporn Chatchawanchanchanakij (My University, 2022)
This study aimed to determine whether the structural equation model accurately predicted the impact of intellectual capital, the creative economy, and the marketing mix on the development of community companies in Thailand during the COVID-19 crisis. In the sample group, the analysis of structural equation models using Kline's (2011) sample size calculations, 200 or more samples were obtained. The researcher collected 230 samples to reduce discrepancies and assigned a simple random selection. The population used in the study consisted of 6,942 members of the community enterprises in area 2 (Sample group). Descriptive statistics include frequency and percentage data, Standard deviation, the arithmetic mean, multivariate statistical analysis, and structural equation modeling (Structural Equation Model). The findings demonstrated that all factors were positively correlated and statistically significant at the 0.05 level. The correlation coefficient ranges from 0.403 to 0.652. The results of the structural equation model's conformity test with the empirical data.
Keywords: Sample (material); Conformity; COVID-19 Pandemic Impacts